Treatment of Brachioradial Pruritus: A Tertiary Center Retrospective Analysis - Kayla D. Mashoudy; Luis F. Andrade; Nicole Khalil; Ellie H. Zhang; Jaxon D. Wagner; Bharat Malhotra; Gil Yosipovitch (Medical Journals Sweden, 2024)
This retrospective study investigates the efficacy of 2 treatment regimens, pregabalin alone versus pregabalin combined with ketamine, amitriptyline, and lidocaine cream, in reducing itch in patients with brachioradial pruritus at a tertiary care center. Electronic medical records of 64 brachioradial pruritus patients seen at the University of Miami Itch Center were analyzed. A significant reduction in itch scores was seen with both treatments, with no significant difference between the groups. A small number of patients experienced adverse effects, including drowsiness and weight gain with pregabalin and skin irritation with ketamine, amitriptyline, and lidocaine cream. Ultimately, our findings underscore the potential of utilizing combined therapy for difficult-to-treat brachioradial pruritus cases and implementing individualized approaches for managing neuropathic pruritus. Further controlled clinical trials are needed to establish optimal treatment protocols.